Immunopathological Basis of Virus-induced Myocarditis - Reinhard Maier; Philippe Krebs; Burkhard Ludewig (Clinical and Developmental Immunology)
Heart diseases are an important cause of morbidity and mortality in industrialized countries. Dilated cardiomyopathy (DCM), one of the most common heart diseases, may be the consequence of infectionassociated myocardits. Coxsackievirus B3 (CVB3) can be frequently detected in the inflamed heart muscle. CVB3-induced acute myocarditis is most likely the consequence of direct virus-induced myocyte damage, whereas chronic CVB3 infection-associated heart disease is dominated by its immunopathological sequelae. Bona fide autoimmunity, for example, directed against cardiac myosin, may favor chronic destructive immune damage in the heart muscle and thereby promote the development of DCM. The immunopathogenesis of myocarditis and subsequent DCM induced either by pathogens or autoantigens can be investigated in well-established animal models. In this article, we review recent studies on the role of viruses, with particular emphasis on CVB3, and different immunological effector mechanisms in initiation and progression of myocarditis.